Managerial Ownership and Capital Structure on Company Value : Intervening by Dividend Policy - Dini, Nur Arifa Sri; Wijaya, Ronni Andri; Sari, Desi Permata (GOVERNORS, 2024)
This study aims to determine managerial ownership and capital structure on company value with dividend policy as an intervening variable in consumer non-cyclicals sector companies listed on the IDX for the 2019-2023 period. The sampling technique used purposive sampling and obtained as many as 20 samples of companies in the consumer non-cyclicals sector. The types of data used were multiple regression analysis and path analysis using SPSS 25. Based on the results of the study, it is shown that partial managerial ownership has unsignificant effect on dividend policy, capital structure partially has a significant effect on dividend policy, partial managerial ownership has a significant effect on company value, capital structure partially has a significant effect on company value, dividend policy partially has a significant effect on company value, dividend policy is can’t moderate the relationship between managerial ownership and company value, dividend policy can’t mediate the influence of capital structure on company value.